Effects of cattle grazing on avian biodiversity and undergrowth vegetation cover in oil palm agriculture - Tohiran, Kamil Azmi (2018)
Expansion of oil palm agriculture in the tropics is driven by its economic success. However, it may cause biodiversity loss if such expansion is permitted without considering environmental protection. Mitigation efforts such as incorporating bio-control agents may reduce this negative impact. Integrating cattle in oil palm plantation to control weeds is expected to improve biodiversity in this agro-ecosystem. While reducing the need for chemical herbicides, it also provides additional food security, ecosystem services, and habitat heterogeneity. Point transect sampling method was used to survey palm oil plantation birds in 45 oil palm plantations which were divided into systematically, un-systematically cattle grazed and control plantations (without cattle grazing). Bird species richness was found increased with size of grazing area, but decreased with number of cattle. Bird abundance was positively related with the systematic grazing system, but was also negatively influenced by number of cattle. Oil palm plantations with systematic or non-systematic cattle grazing had more diverse bird species composition than those without cattle grazing. The bird species composition was determined by four attributes, including the number of cattle, selective weeding frequency, age of oil palm stand, and palm height. Cattle grazing also had a significant positive effect on the height and extent of undergrowth in oil palm plantations, while still suppressing weeds. Therefore, targeted (i.e. systematic rotational) cattle grazing system was concluded can improve bird diversity in the plantations. Therefore, cattle integration with oil palm agriculture for weeds control should be promoted as one step to realize the environmental sustainability goal. It was recommended that a cattle grazing is an excellent way for oil palm stakeholders to improve sustainability and biodiversity in plantations by maintaining constant, manageable undergrowth while reducing their reliance on chemical herbicides.